Repeat-induced abortion and associated factors among reproductive-age women seeking abortion services in South Ethiopia. (September 2022) - Geta, Girma; Seyoum, Kenbon; Gomora, Degefa; Kene, Chala
Introduction: Despite the advances in modern health care, maternal morbidity and mortality remain major problems in Ethiopia. Repeat-induced abortion is an indispensable contributor to this problem. Even though there are adverse effects on health, a significant proportion of Ethiopian women procure more than one abortion during their reproductive lifetime. This study aimed to determine the prevalence and associated factors of repeat-induced abortion in South Ethiopia, in 2020. Methods: An institution-based cross-sectional study design and a systematic random sampling technique were used to collect data from 410 samples of women. Data were collected using pre-tested and semi-structured interviewer-administered questionnaires. The data were coded and entered into EpiData version 4.6.2.0 before being exported to Statistical Package for Social Sciences (SPSS) version 26 for analysis. Variables with a p-value of less than 0.05 in binary logistic regressions were exported into multivariate logistic regression analysis. Finally, variables with a p-value of less than 0.05 in the multivariate logistic regression analysis were used to declare statistical significance. Result: The prevalence of repeat-induced abortion was found to be 35.4% (95% confidence interval = 30.7–40). Not facing a complication in prior abortion care, having more than two partners in the last 12 preceding months, perceiving abortion procedure as non-painful, having a sexual debut before the age of 18 years, and consuming alcohol have higher odds of repeat-induced abortion when compared with their counterparts. Conclusion: The prevalence of repeat-induced abortion in Hawassa city is high compared to studies conducted in other parts of Ethiopia. Not facing complications during previous abortion care, perceiving the abortion procedure as non-painful, alcohol consumption, having multiple sexual partners, and having a sexual debut before the age of 18 years are found to increase the chance of repeat-induced abortion.